Median canaliform nail dystrophy in a 5-year-old child. - Elfatoiki, F.Z.; Saddik, A.; Hali, F.; Chiheb, S. (European Journal of Pediatric Dermatology, 2024)
Median canaliform nail dystrophy usually affects the thumb nail and is characterized by a long median longitudinal ridge that extends from the cuticle to the distal edge of the nail with lateral grooves that resemble the distribution of the branches of a fir tree. A case was described in a 5-year-old child with attention deficit hyperactivity disorder.